Застосування паралельних обчислень у задачах ідентифікації параметрів технологічних процесів - Купін, А. І.; Музика, І. О. (Видавництво Львівської політехніки, 2011)
Possibility of application of parallel calculations in problems of mathematical models identification of static technological objects by regression analysis is considered.
Keywords: regression analysis; parallel calculations; multiprocessor computer